الفن الإسلامي وتأثيره على أعمال فنان الزجاج العالمي إيميل جاليه Émile Galle - إبراهيم، شيماء سلامه (الجمعية العربية للحضارة والفنون الإسلامية, 2016)
Islamic art Excellence features and methods of art mixed with the human reality and the arts become a source of inspiration for many of Western art, which significantly affected the direction of Islamic Art in abstraction and simplification, which calls for the abolition of the picture and strip, hence the Islamic art gateway for many of the modern technical schools such as school abstract and Abstract Expressionism and cubism and brutal and surreal and it appeared evident in the work of numerous acts of international artists . The likes of (Henri Matisse-Picasso-Marc Shigal -Silvador Daly–Kandensky and many others) Islamic art is a school built on the art of calligraphy and art decoration, is French artist glass Emile Galle of the most important artists of the glass in the twentieth century and belonging to the School of Modern Art (Art Novo School), which most of his work was characterized by simplicity and abstraction and softer line, and through the research noted many similarities between the technical direction and decorative works of Galle glass and the distinctive features of Islamic art and from here emerged the problem of search: Research problem: Is the artist Emile Galle influenced by Islamic art in the design and implementation of its glass? Research aim to: To reach the vulnerability of glass artist Emile Galle in Islamic art. -Attempting to detect the relationship between each of Islamic art and aesthetic values of the technology for the production of glass Emile Galle.
تميز الفن الإسلامي بميزات وأساليب فنية امتزجت بالواقع الإنساني وأصبحت فنونه مصدرا ملهما للعديد من الفنون الغربية والتي تأثرت تأثرا كبيرا باتجاه الفن الإسلامي في التجريد والتبسيط التي تطالب بإلغاء الصورة وتجريدها، ومن هنا كان الفن الإسلامي مدخلا للعديد من المدارس الفنية الحديثة كالمدرسة التجريدية والتجريدية التعبيرية والتكعيبية والوحشية والسيريالية، وظهر ذلك جليا في أعمال العديد من أعمال الفنانين العالميين أمثال: (هنري ماتيس – بابلو بيكاسو – مارك شيجال – سلفادور دالي – كاندنسكي وغيرهم الكثير)، الفن الإسلامي هو مدرسة بُنيت على فن الخط وفن الزخرفة، ويعد فنان الزجاج الفرنسي إيميل جاليه من أهم فناني الزجاج في القرن العشرين والمنتمي لمدرسة الفن الحديث(مدرسة الآرت نوفو) والتي تميزت معظم أعماله بالبساطة والتجريد ونعومة الخط، ومن خلال البحث لوحظ العديد من أوجه التشابه بين الاتجاه الفني والزخرفي لأعمال جاليه الزجاجية والسمات المميزة للفن الإسلامي، ومن هنا ظهرت مشكلة البحث المتمثلة في: مشكلة البحث: هل تأثر الفنان إيميل جاليه بالفن الإسلامي ف تصميم وتنفيذ أعماله الزجاجية؟ هدف البحث: - التوصل لمدى تأثر فنان الزجاج إيميل جاليه بالفن الإسلامي. - محاولة الكشف عن العلاقة بين كل من الفن الإسلامي والقيم الجمالية لتكنولوجيا إنتاج الزجاج لإيميل جاليه
Keywords: الزجاج; الزخرفة; الفن الإسلامى; إيميل جاليه